2009
DOI: 10.1016/j.micinf.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the human neutrophil NADPH oxidase by Coxiella burnetii

Abstract: Coxiella burnetii is an obligate intracellular Gram-negative pathogen. A notable feature of C. burnetii is its ability to replicate within acidic phagolysosomes; however, the mechanisms utilized in evading host defenses are not well defined. Here, we investigated human neutrophil phagocytosis of C. burnetii (Nine Mile, phase II; NMII) and the effect of phagocytosed organisms on neutrophil reactive oxygen species (ROS) production. We found that opsonization with immune serum substantially enhanced phagocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 35 publications
0
38
0
1
Order By: Relevance
“…This suggests that neutrophils may not be able to kill C. burnetii directly. It has been shown that C. burnetii uptake by neutrophils decreases the amount of reactive oxygen species (ROS) produced by the neutrophils (24). If the role of neutrophils in C. burnetii infection is not associated with direct killing, there are two other possible roles, based on the increased disease severity observed when neutrophils are depleted: (i) C. burnetii infects neutrophils, which are then taken up by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that neutrophils may not be able to kill C. burnetii directly. It has been shown that C. burnetii uptake by neutrophils decreases the amount of reactive oxygen species (ROS) produced by the neutrophils (24). If the role of neutrophils in C. burnetii infection is not associated with direct killing, there are two other possible roles, based on the increased disease severity observed when neutrophils are depleted: (i) C. burnetii infects neutrophils, which are then taken up by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of response was thought to be caused, in part, by acid phosphatase activity that was detected in C. burnetii extracts (4,25). Recently, Siemsen et al reported that PMN challenged with opsonized NMII did not activate the translocation of p47 phox or p60 phox to the membrane (42). This suggested that C. burnetii actively inhibited the phosphorylation of p47 phox and p60 phox , although it was not determined if C. burnetii components acted directly or indirectly upon p47 phox and p60 phox phosphorylation.…”
mentioning
confidence: 99%
“…Previous work suggests that catalase and SOD are potential persistence factors for Coxiella bacteria residing in the intracellular niche (1,14). In addition, a secreted acid phosphatase possibly reduces the respiratory burst of the host cell by inhibiting NADPH oxidase (4,23). in silico analysis of the C. burnetii RSA 493 genome (22) revealed predicted Mn-and Cu/Zn-SODs, catalase, and four peroxiredoxins (Prxs), which are antioxidant enzymes (EC 1.11.1.15) that are thiol-containing reductants used to detoxify hydroperoxides.…”
mentioning
confidence: 99%